Sainthood and authority in early Islam: Al-Ḥakīm al-Tirmidhī's theory of wilāya and the reenvisioning of the Sunnī Caliphate - Palmer, Aiyub (Studies on Sufism, 2020)
"In Sainthood and Authority in Early Islam Aiyub Palmer recasts wilāya in terms of Islamic authority and traces its development in both political and religious spheres up through the 3rd and 4th Islamic centuries. This book pivots around the ideas of al-Ḥakīm al-Tirmidhī, the first Muslim theologian and mystic to write on the topic of wilāya. By looking at its structural roots in Arab and Islamic social organization, Aiyub Palmer has reframed the discussion about sainthood in early Islam to show how it relates more broadly to other forms of authority in Islam. This book not only looks anew at the influential ideas of al-Tirmidhībut also challenges current modes of thought around the nature of authority in Islamicate societies"--